CsPbBr3 perovskite quantum dot material and preparation method thereof
By using DBSA ligands and replacing DDOAB as OLAB in the perovskite quantum dot synthesis process, the instability of perovskite quantum dot materials in harsh environments is solved, and efficient photoelectric performance and electron transmission efficiency are achieved.
Patent Information
- Application Number
- CN202510166102.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-06-17
- Estimated Expiration
- 2045-02-14
AI Technical Summary
Perovskite quantum dot materials are prone to structural damage and photodegradation under the influence of environmental factors such as light, heat, moisture, and oxygen, resulting in poor and unstable device performance, limiting their practical application in optoelectronic devices.
By changing the ligand, regulating the growth of quantum dots, thereby regulating their morphology and size, the specific method includes replacing DDOAB with oleamine bromine OLAB while using DBSA ligand during quantum dot synthesis to reduce steric hindrance effects and improve the binding force of the ligand.
The higher colloidal structural stability of CsPbBr3 perovskite quantum dot material, the photoluminescent quantum efficiency reaches 85% to 100%, and significantly improves electron transmission efficiency and reduces the power consumption of the device.
Smart Images

Figure CN120158295A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite nanocrystal preparation, and particularly to a CsPbBr3 perovskite quantum dot material and a preparation method thereof. Background Art
[0002] Quantum dot (QD) materials refer to crystalline materials with sizes typically ranging from 2 to 20 nm, which exhibit quantum confinement effects, meaning that their size strongly affects their electronic and optical properties. This quantum confinement effect allows for precise tuning of the electronic bandgap, making QDs suitable for various applications, including solar cells, light-emitting diodes, lasers, and photodetectors, etc., and thus has received extensive attention in the academic and industrial communities. In the past 40 years, the research on QD materials has gone through several stages, including discovery (preliminary scientific exploration), expansion (in-depth basic research), application exploration, and industrialization. With these developments, the QD material series has been greatly expanded, and to date, there are dozens of QD materials in different compound groups. Especially in the past 15 years, perovskite quantum dot (PQD) materials have become favorable candidates to meet different application requirements due to their low cost, excellent stability, high photoluminescence, and high carrier mobility, etc. This perovskite quantum dot (PQD) nanoscale semiconductor material generally has the chemical formula ABX3, where the A-site is usually a monovalent organic cation (CH3NH3 + , CH(NH2)2 + ) or an inorganic cation (Cs +) ), the B-site is a divalent cation (Pb 2+ , Sn 2+ ), and the X-site is a halogen anion (I - , Br - , or Cl -) ). In addition to possessing the basic properties of quantum dot materials, such PQD materials show high efficiency in converting light into electrical energy, so they are particularly valuable in the development of advanced optoelectronic devices. However, in the process of moving towards applications, PQD materials also face many problems. Due to their ionic nature and low formation energy, even the most widely studied class of CsPbX3 quantum dots is prone to environmental degradation caused by light, heat, moisture, oxygen, and other factors, which can damage the structure of the material or cause photodegradation. At the same time, because of the complex ionic structure of perovskite materials, it also promotes their decomposition, and there are multiple crystal polymorphs, resulting in their instability at room temperature. Therefore, devices constructed from PQD materials are prone to the industry problems of poor device performance and unstable operation, which severely limits their practical applications in devices.
[0003] To improve the application potential of perovskite quantum dot optoelectronic devices, the regulation of PQD materials is crucial. In the process of precisely controlling the size, morphology, and composition of PQD nanoparticles, thermal injection method and ligand-assisted reprecipitation method are usually used. Among them, the thermal injection method has been widely recognized due to its precision, scalability, and versatility. Usually, during the synthesis of quantum dots by the thermal injection method, acidic and basic ligands need to be introduced to synergistically control the growth of quantum dots, thereby controlling the morphology and size of quantum dots. Ligands usually act as stabilizers, providing a barrier between individual PQDs and reducing the possibility of particle coalescence. Among them, the introduction of acidic ligands usually anchors Pb 2+ ions to stabilize the lattice structure of perovskite, while the introduction of basic ligands usually anchors halogen X- ions to regulate the morphology. In traditional synthesis, oleic acid (OA) and oleylamine (OLA) ligands are usually used, but their binding effect with the quantum dot surface is not good, making the ligands easily desorb and fall off from the quantum dot surface, resulting in a decline in the optical properties and stability of PQD materials. Therefore, researchers usually use organic ligands with stronger binding ability to solve this problem. For example, in the published article (Ligands for CsPbBr3 perovskite quantum dots: The stronger the better?), dodecylbenzenesulfonic acid (DBSA) was used instead of oleic acid, and dioctadecylammonium bromide (DDOAB) was used instead of oleylamine to synthesize perovskite quantum dots. After that, the stability and optical properties of PQD were significantly enhanced. This benefits from the strong defect passivation effect of the DBSA acidic ligand, which reduces the defect density in the PQD material, thereby reducing the probability of photons being trapped by defects and enhancing its luminescence efficiency. At the same time, due to the steric hindrance effect caused by the long carbon chain of the DDOAB basic ligand, it does not have enough space to act on the quantum dot surface, but only serves as a Br source precursor to provide the Br - ions, which makes DBSA the only ligand for PQD. Because of the strong defect passivation effect of the DBSA ligand, the optical properties and stability of PQD are greatly enhanced, so its photoluminescence quantum efficiency can be greater than 90%. However, the insulating DBSA ligand has a natural local charge shielding effect. The higher the ligand density, the stronger this charge shielding effect, which will reduce the electron tunneling effect between adjacent quantum dots, resulting in a decrease in electron transport efficiency. The external quantum efficiency of its device is only 2.7%. Applying this PQD material with DBSA ligand to the device will instead greatly reduce the electron transport efficiency between devices and increase the power consumption of the device. Generally speaking, using the PQD material with DBSA and DDOAB, sacrificing a part of the electrical properties is behind the excellent optical properties obtained, which is disadvantageous for optoelectronic devices. Summary of the Invention
[0004] In view of this, the present invention provides a CsPbBr3 perovskite quantum dot material and a preparation method thereof, which regulate the growth of quantum dots by changing ligands, and further regulate the morphology and size of quantum dots, so as to obtain the regulation law of ligands on optoelectronic properties, and promote the stability of CsPbBr3 in an air environment and its optoelectronic transport properties.
[0005] In the first aspect, the present invention provides a preparation method of a CsPbBr3 perovskite quantum dot material, comprising the following steps:
[0006] Step 1: Mix cesium carbonate (Cs2CO3), lead acetate (Pb(Ac)2), octadecene (ODE) and dodecylbenzenesulfonic acid (DBSA), and heat under the protection of an inert gas to obtain a precursor solution of cesium source and lead source;
[0007] Step 2: Mix oleylamine (OLA) and hydrogen bromide (HBr) under the protection of an inert gas to obtain an oleylamine bromide (OLAB) precursor solution;
[0008] Step 3: Heat the precursor solution of Step 1, inject it into the oleylamine bromide precursor solution of Step 2, mix and then cool to obtain a crude quantum dot colloid solution;
[0009] Step 4: Centrifuge the crude quantum dot colloid solution of Step 3, add a detergent to the supernatant and centrifuge it twice, and collect the precipitate;
[0010] Step 5: Dry the precipitate collected in Step 4 to obtain the CsPbBr3 perovskite quantum dot material.
[0011] Based on the above technical solutions, preferably, in Step 1, the dosage ratio of cesium carbonate, lead acetate, octadecene and dodecylbenzenesulfonic acid is (0.08 - 0.12) g: 0.076 g: (5 - 20) ml: (0.5 - 1) ml.
[0012] Based on the above technical solutions, preferably, in Step 1, the heating temperature is 100 - 120 °C, and the heating time is 0.5 - 1 h.
[0013] Based on the above technical solutions, preferably, in Step 2, the volume ratio of oleylamine to hydrogen bromide is 10 ml: 1 ml.
[0014] Based on the above technical solutions, preferably, in Step 2, the mixing temperature is 100 - 120 °C, and the mixing time is 0.5 - 1 h.
[0015] Based on the above technical solutions, preferably, in Step 3, the reaction temperature is 145 - 175 °C, and the reaction time is 10 - 30 s.
[0016] On the basis of the above technical solutions, preferably, in step four, the addition amount of the detergent is 2 to 3 times the volume of the supernatant.
[0017] On the basis of the above technical solutions, preferably, in step four, the rotation speed of the secondary centrifugation is 7000 - 8500 rpm.
[0018] In a second aspect, the present invention relates to a CsPbBr3 perovskite quantum dot material prepared by the above method.
[0019] A CsPbBr3 perovskite quantum dot material and a preparation method thereof provided by the present invention have the following beneficial effects compared with the prior art:
[0020] (1) The surface ligands (OLAB and DBSA) of the cesium lead bromide quantum dots prepared by the present invention can form a strong binding force with the quantum dots and are not easily detached, thus showing higher colloidal structural stability.
[0021] (2) The optical properties (photoluminescence quantum yield PLQY) and electrical properties (electron transport efficiency) of the cesium lead bromide quantum dots prepared by the present invention are simultaneously improved. Its PLQY is as high as 85% - 100%, and the volume resistance value of its device thin film is less than 100 Ω, which is nearly 10 times higher than the resistance value of the quantum dot thin film device passivated with DDOAB ligand and DBSA ligand in the prior art, indicating that its electron transport efficiency is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the following drawings are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.
[0023] Figure 1 It is a schematic flow chart of preparing a CsPbBr3 quantum dot sample in Example 2 of the present invention;
[0024] Figure 2 It is a high-resolution transmission electron microscope atomic image structure diagram of the CsPbBr3 quantum dots prepared in Example 2 of the present invention;
[0025] Figure 3 It is a high-resolution transmission electron microscope image of the CsPbBr3 quantum dots prepared in Examples 1 - 3 and Comparative Examples 1 - 2 of the present invention;
[0026] Figure 4 It is a high-resolution transmission electron microscope image of the CsPbBr3 quantum dots prepared in Comparative Example 3 and Comparative Example 4 of the present invention;
[0027] Figure 5 These are the PL test graphs of the CsPbBr3 quantum dots prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention;
[0028] Figure 6 These are the PLQY test graphs of the CsPbBr3 quantum dots prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention;
[0029] Figure 7 These are the physical pictures of the CsPbBr3 quantum dot powder prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention dissolved in n-hexane;
[0030] Figure 8 These are the schematic diagrams of the CsPbBr3 quantum dot device structures prepared in Example 2 and Comparative Example 3 of the present invention;
[0031] Figure 9 These are the electrical test graphs of the quantum dot thin film devices prepared in Example 2 and Comparative Example 3 of the present invention;
[0032] Figure 10 These are the XRD test graphs of the CsPbBr3 quantum dots prepared in Examples 1-3 of the present invention;
[0033] Figure 11 These are the FTIR spectra of the CsPbBr3 quantum dots prepared in Example 2 of the present invention. Detailed implementation manners
[0034] Next, in combination with the implementation manners of the present invention, the technical solutions in the implementation manners of the present invention will be clearly and completely described. Obviously, the described implementation manners are only a part of the implementation manners of the present invention, rather than all the implementation manners. Based on the implementation manners in the present invention, all other implementation manners obtained by those of ordinary skill in the art without making creative efforts belong to the scope of protection of the present invention.
[0035] In the process of exploring how to improve the optoelectronic performance of perovskite quantum dot (PQD) optoelectronic devices, the inventors found that: when using the ligand-assisted reprecipitation method in the prior art, organic ligands with stronger binding ability are usually considered to achieve "strong-strong binding". This strategy refers to modifying the surface of PQDs by selecting ligands with higher binding energy and stronger stability, so as to passivate surface defects more effectively, improve the stability and optical properties of quantum dots. For example, ligands such as dodecylbenzenesulfonic acid (DBSA) and dioctadecylammonium bromide (DDOAB) with stronger binding ability than traditional oleic acid (OA) and oleylamine (OLA) are used. The advantages of adopting this strategy are as follows: First, ligands with strong binding ability can effectively passivate the surface defects of PQDs, reduce the trap state density caused by surface dangling bonds, and thus greatly improve the photoluminescence quantum yield (PLQY). Second, such ligands improve the dispersibility of PQDs in solution, reduce the aggregation phenomenon between particles, and help to prepare a uniform and high-quality thin film, which is crucial for manufacturing efficient and stable optoelectronic devices. Finally, due to the stronger interaction between the ligand and PQD, the environmental stability of the material is enhanced, including humidity resistance, thermal stability and light stability, which enables PQD-based devices to maintain high performance under a wider range of conditions.
[0036] However, the inventors found in the practice process that the above effects can be achieved not only through "strong-strong binding". The inventors of this application further regulated the growth of quantum dots by changing the ligand, and then regulated the morphology and size of the quantum dots, so as to obtain the regulation law of the ligand on the optoelectronic performance. The specific implementation process is as follows: During the synthesis of quantum dots, while using the DBSA ligand, dioctadecylammonium bromide (DDOAB) is replaced by oleylamine bromide (OLAB). This replacement of the double-chain DDOAB with the single-chain OLAB reduces the steric hindrance effect brought by the long carbon chain, enabling OLAB to bind to the surface of perovskite quantum dots. In this way, the morphology of perovskite quantum dots is regulated, changing the original hexahedral structure into a dodecahedral structure, and obtaining ultra-high optical properties. The experimental results show that the adjusted method can make the photoluminescence quantum efficiency (PLQY) of PQDs as high as 96%, far superior to the 40% - 80% of traditional oleic acid and oleylamine ligand quantum dots. More importantly, although the weakly binding OLAB ligand is easily peeled off from the surface of the quantum dots during the post-treatment process, the strongly binding DBSA ligand can remain stable, which not only reduces the ligand density of the quantum dots but also maintains high optical performance. This method effectively enhances the electron transport efficiency in PQD devices and avoids problems such as the decrease in electron tunneling efficiency caused by excessive charge screening effects.
[0037] The technical solution for preparing CsPbBr3 perovskite quantum dot materials of the present invention is achieved through the following steps:
[0038] Step 1: Mix cesium carbonate, lead acetate, octadecene, and dodecylbenzenesulfonic acid, and heat under the protection of an inert gas, which helps to remove water and oxygen to prevent material oxidation and dissolve the cesium carbonate and lead acetate powders to form a stable precursor solution of cesium source and lead source;
[0039] Step 2: Mix oleylamine and hydrogen bromide under the protection of an inert gas to obtain an oleylammonium bromide precursor solution;
[0040] Step 3: Heat the precursor solution in Step 1 and then inject it into the oleylammonium bromide precursor solution in Step 2, mix and react for a certain time, and then cool it to room temperature in an ice-water bath to obtain a crude quantum dot colloid solution;
[0041] Step 4: Centrifuge the crude quantum dot colloid solution in Step 3, collect the supernatant to remove the incompletely reacted precipitate, add a detergent to the supernatant and then centrifuge it again, collect the precipitate, and this process can be repeated 2 - 3 times to remove the free ligands;
[0042] Step 5: Dry the precipitate collected in Step 4 to obtain the CsPbBr3 perovskite quantum dot material.
[0043] The following further describes the present invention in combination with specific embodiments. The protection scope of the present invention is not limited by the following embodiments. Unless otherwise specified, the main materials involved in the following examples are all commercially available products.
[0044] Example 1
[0045] The CsPbBr3 perovskite quantum dot material of this example is prepared by the following steps:
[0046] Step 1: Mix cesium carbonate, lead acetate, octadecene, and dodecylbenzenesulfonic acid according to a dosage ratio of 0.1 g: 0.076 g: 10 mL: 1 mL, and heat at 100 °C for 1 h under the protection of nitrogen to obtain a precursor solution containing cesium source and lead source;
[0047] Step 2: Mix oleylamine and hydrogen bromide according to a volume ratio of 10 ml: 1 ml in an argon environment at 120 °C for 1 h to obtain an oleylammonium bromide precursor solution;
[0048] Step 3: Heat the precursor solution containing cesium source and lead source in Step 1 to 150 °C, immediately inject 1 ml of the oleylammonium bromide precursor solution in Step 2, mix for 20 s, and then cool it to room temperature in an ice-water bath to obtain a crude quantum dot colloid solution;
[0049] Step 4: Centrifuge the crude quantum dot colloid solution from Step 3 at a speed of 7800 rpm for 5 min, collect the supernatant to remove the incompletely reacted precipitate, add methyl acetate with a volume twice that of the supernatant to the supernatant, perform secondary centrifugation at a speed of 7500 rpm for 5 min, collect the precipitate generated after centrifugation, and repeat the operation of secondary centrifugation three times to remove the free ligands;
[0050] Step 5: Take out the precipitate collected in Step 4 after drying under vacuum at 40 °C for 12 h, and thus obtain the CsPbBr3 perovskite quantum dot material.
[0051] Example 2
[0052] Refer to the appendix Figure 1 , and the CsPbBr3 perovskite quantum dot material of this example is prepared through the following steps:
[0053] Step 1: Mix cesium carbonate, lead acetate, octadecene, and dodecylbenzenesulfonic acid according to a dosage ratio of 0.1 g: 0.076 g: 10 mL: 1 mL, heat at 120 °C for 30 min under the protection of argon to obtain a precursor solution containing cesium source and lead source;
[0054] Step 2: Mix oleylamine and hydrogen bromide in a volume ratio of 10 ml: 1 ml in an argon environment at 120 °C for 1 h to obtain an oleylammonium bromide precursor solution;
[0055] Step 3: After heating the precursor solution containing cesium source and lead source in Step 1 to 165 °C, immediately inject 1 ml of the oleylammonium bromide precursor solution in Step 2, mix for 20 s, and then cool to room temperature in an ice-water bath to obtain a crude quantum dot colloid solution;
[0056] Step 4: Centrifuge the crude quantum dot colloid solution from Step 3 at a speed of 7800 rpm for 5 min, collect the supernatant to remove the incompletely reacted precipitate, add ethyl acetate with a volume twice that of the supernatant to the supernatant, perform secondary centrifugation at a speed of 7500 rpm for 5 min, collect the precipitate generated after centrifugation, and repeat the operation of secondary centrifugation twice to remove the free ligands;
[0057] Step 5: Take out the precipitate collected in Step 4 after drying under vacuum at 40 °C for 16 h, and thus obtain the CsPbBr3 perovskite quantum dot material.
[0058] Example 3
[0059] The CsPbBr3 perovskite quantum dot material of this example is prepared through the following steps:
[0060] Step 1: Mix cesium carbonate, lead acetate, octadecene, and dodecylbenzenesulfonic acid in a dosage ratio of 0.1 g: 0.076 g: 10 mL: 1 mL, and heat at 100 °C for 1 h under the protection of nitrogen to obtain a precursor solution containing cesium source and lead source;
[0061] Step 2: Mix oleylamine and hydrogen bromide in a volume ratio of 10 ml: 1 ml in an argon environment at 120 °C for 1 h to obtain an oleylammonium bromide precursor solution;
[0062] Step 3: After heating the precursor solution containing cesium source and lead source in Step 1 to 175 °C, immediately inject 1 ml of the oleylammonium bromide precursor solution in Step 2, mix for 20 s, and then cool to room temperature in an ice-water bath to obtain a crude quantum dot colloidal solution;
[0063] Step 4: Centrifuge the crude quantum dot colloidal solution in Step 3 at a speed of 7800 rpm for 5 min, collect the supernatant to remove the incompletely reacted precipitate, add methyl acetate with a volume twice that of the supernatant to the supernatant, and perform secondary centrifugation at a speed of 7500 rpm for 5 min. Collect the precipitate generated after centrifugation, and repeat the operation of secondary centrifugation twice to remove free ligands;
[0064] Step 5: Dry the precipitate collected in Step 4 under vacuum at 40 °C for 20 h, and then take it out to obtain the CsPbBr3 perovskite quantum dot material.
[0065] Example 4
[0066] The CsPbBr3 perovskite quantum dot material of this example is prepared through the following steps:
[0067] Step 1: Mix cesium carbonate, lead acetate, octadecene, and dodecylbenzenesulfonic acid in a dosage ratio of 0.08 g: 0.076 g: 5 mL: 0.5 mL, and heat at 120 °C for 30 min under the protection of nitrogen to obtain a precursor solution containing cesium source and lead source;
[0068] Step 2: Mix oleylamine and hydrogen bromide in a volume ratio of 10 ml: 1 ml in an argon environment at 100 °C for 2 h to obtain an oleylammonium bromide precursor solution;
[0069] Step 3: After heating the precursor solution containing cesium source and lead source in Step 1 to 145 °C, immediately inject 1 ml of the oleylammonium bromide precursor solution in Step 2, mix for 30 s, and then cool to room temperature in an ice-water bath to obtain a crude quantum dot colloidal solution;
[0070] Step 4: Centrifuge the crude quantum dot colloid solution from Step 3 at a speed of 7800 rpm for 5 min, collect the supernatant to remove the incompletely reacted precipitate, add methyl acetate in an amount three times the volume of the supernatant to the supernatant, perform secondary centrifugation at a speed of 7000 rpm for 5 min, collect the precipitate generated after centrifugation, and repeat the operation of secondary centrifugation three times to remove the free ligands;
[0071] Step 5: Take out the precipitate collected in Step 4 after drying under vacuum at 40 °C for 24 h, and thus obtain the CsPbBr3 perovskite quantum dot material.
[0072] Example 5
[0073] The CsPbBr3 perovskite quantum dot material of this example is prepared through the following steps:
[0074] Step 1: Mix cesium carbonate, lead acetate, octadecene, and dodecylbenzenesulfonic acid in a dosage ratio of 0.12 g: 0.076 g: 20 mL: 1 mL, and heat at 120 °C for 30 min under the protection of nitrogen to obtain a precursor solution containing cesium source and lead source;
[0075] Step 2: Mix oleylamine and hydrogen bromide in a volume ratio of 10 ml: 1 ml in an argon environment at 120 °C for 1 h to obtain an oleylammonium bromide precursor solution;
[0076] Step 3: After heating the precursor solution containing cesium source and lead source in Step 1 to 165 °C, immediately inject 1 ml of the oleylammonium bromide precursor solution in Step 2, mix for 30 s, and then cool to room temperature in an ice-water bath to obtain a crude quantum dot colloid solution;
[0077] Step 4: Centrifuge the crude quantum dot colloid solution from Step 3 at a speed of 7800 rpm for 5 min, collect the supernatant to remove the incompletely reacted precipitate, add methyl acetate in an amount twice the volume of the supernatant to the supernatant, perform secondary centrifugation at a speed of 8500 rpm for 5 min, collect the precipitate generated after centrifugation, and repeat the operation of secondary centrifugation twice to remove the free ligands;
[0078] Step 5: Vacuum-dry the precipitate collected in Step 4 to obtain the CsPbBr3 perovskite quantum dot material.
[0079] Comparative Example 1
[0080] The difference from Example 2 is that: in Step 3, the mixing temperature is 140 °C. The remaining steps remain unchanged.
[0081] Comparative Example 2
[0082] The difference from Example 2 is that: in Step 3, the mixing temperature is 185 °C. The remaining steps remain unchanged.
[0083] Comparative Example 3
[0084] The difference from Example 2 is as follows: Step two is omitted. Meanwhile, in Step three, after heating the precursor solution of the cesium source and the lead source in Step one to 165°C, 1 ml of DDOAB in Step two is immediately injected. The remaining steps remain unchanged.
[0085] Comparative Example 4
[0086] The CsPbBr3 perovskite quantum dot material of this comparative example is prepared by the following steps:
[0087] Step one: Dissolve 0.1468 g of lead bromide in 10 ml of 1-octadecene, stir and heat to 120°C under argon protection, add 2 ml of oleic acid (OA) and oleylamine (OLA), and heat at 120°C for 30 min under nitrogen protection to obtain a precursor solution containing a bromine source and a lead source;
[0088] Step two: Mix 0.652 g of cesium carbonate and 10 ml of oleic acid, and mix at 120°C for 1 h in an argon atmosphere to obtain a cesium oleate precursor solution;
[0089] Step three: Heat the solution in Step one to 165°C, then quickly inject 1 ml of cesium oleate precursor (Cs-OA) solution and mix for 8 s, and then cool to room temperature in an ice-water bath to obtain a crude quantum dot colloid solution;
[0090] Step four: Centrifuge the crude quantum dot colloid solution in Step three at a speed of 7800 rpm for 5 min, collect the supernatant to remove incompletely reacted precipitates, add methyl acetate with a volume twice that of the supernatant to the supernatant, and perform secondary centrifugation at a speed of 8500 rpm for 5 min. Collect the precipitate generated after centrifugation, and repeat the operation of secondary centrifugation twice to remove free ligands;
[0091] Taking the above Examples 1 to 3 and Comparative Examples 1 to 4 as examples, the following performance tests are carried out, and the test results and analyses are all recorded as follows:
[0092] (1) Transmission electron microscopy test
[0093] Perform high-resolution transmission electron microscopy characterization on the CsPbBr3 quantum dot powder prepared in the above exemplary examples and comparative examples to analyze the sample morphology and size. The test results are as Figures 2 to 4 shown.
[0094] It can be Figure 2 seen that the CsPbBr3 quantum dots observed by transmission electron microscopy in Example 2 are hexagons in the figure, and their three-dimensional structure is a dodecahedron.
[0095] It can be seen from Figure 3 that: at a synthesis temperature of 140 °C, the quantum dot sample size of Comparative Example 1 is too small, indicating that the growth of the quantum dot nanoclusters is incomplete; at the same time, at a synthesis temperature of 185 °C, the quantum dot sample size of Comparative Example 2 is too large, indicating that the high temperature causes the quantum dots to start to agglomerate; therefore, the synthesis temperature range of the dodecahedral CsPbBr3 quantum dots passivated by OLAB and DBSA ligands is between 150 °C and 175 °C.
[0096] It can be seen from Figure 4 that: the morphology sizes of Comparative Example 3 and Comparative Example 4 are both quadrilateral, corresponding to a hexahedron in the three-dimensional space structure. This shows that under the same temperature conditions, only the use of OLAB and DBSA ligands for passivation can achieve the dodecahedral CsPbBr3 quantum dot structure.
[0097] (2) Tests of PL and PLQY
[0098] Take 10 mg of the CsPbBr3 quantum dot powder prepared in the above corresponding examples and comparative examples and pour it into a cuvette, add 4 mL of n-hexane, and gently shake to promote its dissolution. Then place the cuvette in the photoluminescence spectrometer EI-FLS1000 for PL testing. Select the PL test module to obtain its PL emission intensity, and use an integrating sphere to measure the PLQY, and combine the test software to count the PLQY value. The test results are shown in Figures 5 - 6.
[0099] It can be seen from Figure 5 (i) that: the PL test results of the samples prepared in Examples 1 - 3 all show that they all have similar green light emission wavelengths, and the emission position wavelength is between 515 - 520 nm; among them, the PL intensity of the green light emission intensity in Example 2 is the highest, indicating its best optical performance.
[0100] It can be seen from Figure 5 (ii) that: Figure (a) shows that the quantum dots prepared in Comparative Example 1 have a blue shift of the absorption peak due to the small size, and Figure (b) shows that the quantum dots prepared in Comparative Example 2 have a red shift of the absorption peak due to the large size; the PL test pattern of the quantum dots in Figure (c) is equivalent to the PL test pattern of the quantum dots prepared in Example 2, both showing extremely high PL emission intensity, and the PL emission intensity in Figure (d) of the quantum dots prepared in Comparative Example 4 is increased by nearly 3 times.
[0101] It can be seen from Figure 6 (a) that: the CsPbBr3 quantum dots in Examples 1 - 3 show extremely high PLQY values, generally higher than 90%; at the same time, Example 2 shows a PLQY value close to 96%, indicating that Example 2 shows the best optical performance.
[0102] It can be seen from Figure 6(b) It can be seen that the PLQY values of the samples with DBSA ligands are all higher than those of Comparative Example 4, indicating that the DBSA ligand is effective in improving the optical properties; the CsPbBr3 quantum dots in Example 2 exhibit extremely high PLQY values, which are similar to but better than those of Comparative Example 3; at the same time, due to the change in size, the PLQY values of Comparative Example 1 and Comparative Example 2 decrease, representing the deterioration of their optical properties.
[0103] (3) Electron transport efficiency test
[0104] For the CsPbBr3 quantum dot powders prepared in the above exemplary embodiments and comparative examples, devices are fabricated, including the following steps:
[0105] a. Refer to Figure 7 , take 50 mg of quantum dot powder and place it in a 5 mL centrifuge tube, add 2 mL of n-hexane to dissolve the powder to obtain a highly dispersed CsPbBr3 quantum dot solution;
[0106] b. Ultrasonically clean the ITO glass successively with acetone, alcohol, and water for 10 min, then take it out after drying in a vacuum drying oven at 80 °C, put it into a plasma instrument for 10 min of plasma surface treatment (the purpose is to increase surface activity and facilitate spin coating into a film), and after it ends, take it out and use it as the substrate for the spin-coated quantum dot solution;
[0107] c. Place the ITO glass treated in step b on a spin coating instrument, use a pipette to take 50 μL of the quantum dot solution prepared in step a, drop it on the ITO glass, and start the instrument to spin coat into a film.
[0108] d. Use magnetron sputtering to prepare the top electrode for the spin-coated quantum dot film, and then the device encapsulation can be completed.
[0109] The schematic diagrams of the CsPbBr3 quantum dot device structures prepared in Example 2 and Comparative Example 3 are as Figure 8 shown. Based on the test results of performance test (2), further test analysis is carried out on Example 2 and Comparative Example 3. By their respective electron transport efficiencies, the excellent electrical properties of the CsPbBr3 quantum dot powders prepared in Example 2 and Comparative Example 3 are deeply evaluated. On the basis of the above steps a to d, the following steps are also included:
[0110] e. Test the I-V characteristic curves of the above devices through a 4200 semiconductor tester.
[0111] The test results are as Figures 7 to 9 shown.
[0112] Figure 7(a) shows the physical pictures of the CsPbBr3 quantum dot powders prepared from Comparative Example 1, Example 1, Example 2, Example 3, Comparative Example 2, Comparative Example 3, and Comparative Example 4 dissolved in n-hexane from left to right; Figure 7 (b) shows the fluorescence effect pictures of the corresponding physical pictures under ultraviolet light. It can be seen from the above two groups of pictures that the CsPbBr3 quantum dot powders prepared in the examples and comparative examples all have good colloidal stability. Among them, the CsPbBr3 quantum dot powders prepared in Examples 1 to 3 have more excellent fluorescence effects.
[0113] It is Figure 9 known that the current response window of Example 2 is higher than that of Comparative Example 3, and it has increased by nearly 10 times, further indicating that Example 2 has more excellent electron transport efficiency.
[0114] (4) XRD test
[0115] XRD tests were carried out on the quantum dot powders prepared in Examples 1 to 3 to study their crystal structures. The test results are as Figure 10 shown.
[0116] It is Figure 10 known that in the temperature range of 150 °C to 175 °C, the samples prepared in Examples 1 to 3 all show XRD peaks of crystal plane characteristics such as (100), (110), (111), (200), (210), (211), (202), (103), etc., proving that CsPbBr3 quantum dots can be successfully prepared in this temperature range.
[0117] (5) FTIR spectrum test
[0118] Taking Example 2 as an example, FTIR spectrum tests were carried out. The test results are as Figure 11 shown.
[0119] It is Figure 11 known that through FTIR spectra, it shows that there are bending and stretching vibrations of sulfonic acid groups (S=O / S-O) near 1000 - 1380 cm -1 . This indicates that the DBSA ligand has successfully passivated on the surface of the CsPbBr3 quantum dot sample in Example 2; while there is a bending vibration absorption peak of (N-H) near 1650 cm -1 . This indicates that the OLAB ligand has successfully passivated on the surface of the CsPbBr3 quantum dot sample in Example 2.
[0120] In summary, the method for preparing CsPbBr3 perovskite quantum dot materials of the present invention realizes the regulation of the morphology of perovskite quantum dots. Not only is it obtained with ultra-high optical properties, and its photoluminescence quantum efficiency (PLQY) is as high as 96%, which is superior to 40%-80% of traditional oleic acid and oleylamine ligand quantum dots; it also reduces the ligand density of quantum dots, thereby effectively enhancing the electron transport efficiency of PQD devices.
[0121] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing CsPbBr3 perovskite quantum dot material, characterized in that: The following steps are involved: Step 1: mixing cesium carbonate, lead acetate, octadecene and dodecylbenzene sulfonic acid, and heating under the protection of an inert gas to obtain a precursor solution of a cesium source and a lead source; Step 2: mixing oleylamine and hydrogen bromide under the protection of an inert gas to obtain an oleylamine bromide precursor solution; Step 3, after heating the precursor solution of step 1, injecting the ammonium bromide precursor solution of step 2, mixing and then cooling, to obtain a quantum dot colloid crude solution; Step 4: centrifuge the crude quantum dot colloid solution of step 3, add detergent to the supernatant and centrifuge for a second time to collect the precipitate; Step 5: Dry the precipitate collected in step 4 to obtain CsPbBr3 perovskite quantum dot material.
2. The method for preparing the CsPbBr3 perovskite quantum dot material according to claim 1, characterized in that: In step 1, the usage ratio of cesium carbonate, lead acetate octadecene and dodecylbenzene sulfonic acid is (0.08-0.12) g: 0.076 g: (5-20) ml: (0.5-1) ml.
3. The method for preparing the CsPbBr3 perovskite quantum dot material according to claim 2, characterized in that: In step 1, the heating temperature is 100-120° C., and the heating time is 0.5-1 h.
4. The method for preparing the CsPbBr3 perovskite quantum dot material according to claim 1, characterized in that: In step 2, the volume ratio of oleylamine to hydrogen bromide is 10 ml:1 ml.
5. The method for preparing the CsPbBr3 perovskite quantum dot material according to claim 4, characterized in that: In step 2, the mixing temperature is 100-120° C., and the mixing time is 0.5-1 h.
6. The method for preparing the CsPbBr3 perovskite quantum dot material according to claim 1, characterized in that: In step 3, the reaction temperature is 145-175° C., and the reaction time is 10-30 seconds.
7. The method for preparing the CsPbBr3 perovskite quantum dot material according to claim 6, characterized in that: In step 4, the amount of detergent added is 2 to 3 times the volume of the supernatant.
8. The method for preparing the CsPbBr3 perovskite quantum dot material according to claim 7, characterized in that: In step 4, the rotation speed of the secondary centrifugation is 7000-8500 rpm.
9. A CsPbBr3 perovskite quantum dot material, characterized in that: The quantum dot material is prepared by the preparation method of the CsPbBr3 perovskite quantum dot material according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing efficient and stable inorganic perovskite quantum dots by using double-layer ligand
CN112175613A
Preparation method for improving stability of perovskite quantum dots
CN112574738A
Tin oxide / Cs3Bi2Br9 perovskite quantum dot ladder type heterojunction composite photocatalyst as well as preparation method and application thereof
CN116786142A
Perovskite luminescent nanocrystal, light emitting device, and manufacturing method for perovskite luminescent nanocrystal
US20200248070A1